Estimating US Fiscal and Monetary Interactions in a Time Varying VAR - Eddie Gerba; Klemens Hauzenberger (University of Kent, School of Economics, 2013)
We contribute to the growing empirical literature on monetary and fiscal interactions by applying a sign restriction identification scheme to a structural TVP-VAR in order to disentangle and evaluate the policy shocks and policy transmissions. This in turn allows us to study the Great Recession in a consistent fashion. Four facts stand out from our findings. We observe significant differences in the endogenous responses to shocks in particular between the Volcker period and the Great Recession, and find that monetary policy reacts more aggressively during Volcker chairmanship and fiscal policy during the Great Recession to stabilize the economy. Second, impulse responses confirm that there is a high degree of interactions between monetary and fiscal policies over time. Third, in the forecast error variance decomposition we find that while government revenues largely influence decisions on government spending, government spending does not influence tax decisions. Fourth and final, our analysis of the fiscal transmission channel reveals that tax cuts, because of their crowding-in effects, are more effective in expanding output than government spending rises, since the tax multiplier is higher and more persistent. In light of the current recession and the zero lower bound of the interest rate, tax cuts can, by providing the right incentives to the private sector, result in high and very persistent growth in output if private agent expectations regarding the length and the financing structure of the fiscal expansion are delicately managed jointly by the two authorities.
Keywords: C11; C32; E52; E61; E62; E63; 330; time varying parameter VAR; sign restrictions; Markov-Chain Monte Carlo; US economic structure; fiscal transmission channel